Management Pattern of Marriage Registrar Assistant Officer in Indonesia: an Example from Bandung, West Java - Harry Yuniardi (Indonesian Journal of Law and Economics Review, 2019)
The purpose of this study was to find out how the pattern of human resource management Assistant Registrar of Marriage Registrar (P3N) in KUA Cimaung District, Bandung Regency. This study uses field research, with the technique of collecting data through observation and interviews with related parties, namely the Head of KUA, Cimaung District and Head of KUA, Pangalengan District, Guidance Section for Islamic Community, Ministry of Religion Office Bandung and P3N in the Cimaung District and Pangalengan Districts. The results of this study are that the HR management pattern of the Registrar’s Employee Assistance Officer (P3N) in Cimaung District KUA is good and follows excellent management standards, as reflected in the recruitment process until the supervision phase. The admission procedure is carried out in stages from the village, sub-district and district level.